Third Five-Year Plan Punjab State Annual Plan 1962-63 - Planning Commission (Planning Commission, 1962)
In terms of financial outlay as well as physical targets the Third Five-Year Plan represents a much more ambitious programme than either of the first two Plans. While the first Plan provided an outlay of Rs 140.92 crores and the Second Plan was of the order of Rs 163 crores, the Third Plan has been placed at Rs 231 crores. As to the annual plan for 1962-63 the consideration which have weighed in determining its size have been the tempo of progress already achieved during the Second Plan period and the first year of the Third Plan period, the priorities indicated by the State Planning Committee and the phasing outlined by the Planning Commission for the successive years of the Plan.
Planning Department